Binge Drinking Among Older Adults in the United States, 2015 to 2017 - Han, Benjamin H. (J Am Geriatr Soc, 2019)
OBJECTIVES: Binge drinking is a risk factor for a range of harms. This study estimates the national prevalence of binge drinking and adds to our understanding of correlates of binge drinking among older adults in the United States. DESIGN: Cross-sectional analysis. SETTING/PARTICIPANTS: A total of 10 927 adults, aged 65 years or older, from the 2015 to 2017 administrations of the US National Survey on Drug Use and Health. MEASUREMENTS: We estimated the prevalence of past-month binge alcohol use (five or more drinks on the same occasion for men and four or more drinks on the same occasion for women). Characteristics of past-month binge drinkers, including demographics, substance use, serious mental illness, mental health treatment utilization, chronic disease, and emergency department (ED) use, were compared to participants who reported past-month alcohol use without binge drinking. Comparisons were made using χ(2) tests. We then used multivariable generalized linear models using Poisson and log link to examine the association between covariates and binge drinking among all past-month alcohol users aged 65 years or older. RESULTS: Of 10 927 respondents, 10.6% (95% CI = 9.9%–11.2%) were estimated to be current binge drinkers. Binge drinkers were more likely to be male, have a higher prevalence of current tobacco and/or cannabis use, and have a lower prevalence of two or more chronic diseases compared to nonbinge drinkers. In multivariable analysis, among past-month alcohol users, the prevalence of binge drinking was higher among non-Hispanic African Americans than whites (adjusted prevalence ratio [aPR] = 1.44; 95% CI = 1.16–1.80), tobacco users(aPR =1.52; 95%CI=1.33–1.74), cannabis users (aPR = 1.41; 95% CI = 1.11–1.80), and those who visited the ED in the past year (aPR=1.16;95%CI=1.00–1.33). CONCLUSION: Over a tenth of older adults in the United States are estimated to be current binge drinkers. Results confirm the importance of screening for binge drinking behaviors among older adults to minimize harms.